Analisis Nilai Koefisien Absorpsi Bunyi Material Akustik Dari Kulit Kacang Tanah (Arachis Hypogaea) Sebagai Pengendali Kebisingan Menggunakan Metode Tabung Impedansi - Imdani, Khesya Namira; Nurlaela Rauf (Universitas Islam Negeri Alauddin Makassar, 2025)
This research aims to analyze the effect of sample thickness on the sound absorption coefficient of a composite material based on peanut shells and epoxy resin using the impedance tube method. The composites were tested in three thickness variations, namely 1 cm, 2 cm, and 3 cm, to determine the effect of thickness on the material's ability to absorb sound waves in the frequency range of 200–1600 Hz. The test results indicate that an increase in material thickness is directly proportional to an increase in the sound absorption coefficient value. At a thickness of 1 cm, the maximum α value of 0.11 increased to 0.34 at a thickness of 2 cm and reached 0.78 at a thickness of 3 cm. The acoustic material showed the best performance at a frequency of 1600 Hz with a thickness of 3 cm. This indicates that peanut shells have the potential as an environmentally friendly acoustic material alternative.